'We have been left to go it alone': the well-being of family carers of older people during the 2020 COVID-19 pandemic in Wales' - Maria Cheshire-Allen (Social Policy Review, 2021)
While it has become something of a cliche to say that the experience of the COVID-19 pandemic has laid bare hitherto under-recognised patterns of disadvantage in the UK, the light rarely shines on the situations of family carers. This article addresses this gap. It reports on primary data based on 30 semi-structured interviews with family carers living in Wales. Through analysis informed by a critical ethics of care approach, it reveals a context of continuing tensions experienced by carers - tensions that have in key respects been exacerbated by policy responses to the pandemic. We find that in offering protection towards care-receivers, typically along the lines of a medical model, these responses have - among their other implications - often served to undermine the agency of both care-receiver and caregiver and reinforce a discourse in which care is confirmed as a burden, rather than as contributing to well-being. Shining a light on these aspects of the pandemic experience, we argue, offers an opportunity to redefine what well-being for family carers means.